Immunotherapy resistance in triple-negative breast cancer: Molecular mechanisms, tumor microenvironment, and therapeutic implications - Zhou, Zijian; Zhou, Qin (Frontiers in Oncology, 2025)
Triple-negative breast cancer (TNBC) is a unique subtype of breast cancer characterized by high invasiveness, high metastasis rates, and poor prognosis, making it an important focus within global malignancies. Due to the absence of estrogen receptor, progesterone receptor, and HER2 expression, TNBC presents significant challenges in treatment. Metastatic progression markedly increases treatment complexity, drastically reducing patient survival rates. The metastatic and drug resistance processes of TNBC involve complex, multi-step biological mechanisms regulated through various molecular mechanisms and signaling pathways within and outside tumor cells. In recent years, immunotherapy has brought new hope for TNBC. Compared to other breast cancer subtypes, TNBC demonstrates higher immunogenicity, often accumulating a higher mutational burden that generates more neoantigens, thus typically resulting in a tumor microenvironment (TME) enriched with tumor-infiltrating lymphocytes (TILs). Additionally, PD-L1 expression is significantly higher in TNBC compared to other subtypes, closely correlating with TIL abundance. These characteristics position TNBC as a strong candidate for immune checkpoint inhibitor (ICI) therapy. Clinical trials have demonstrated promising efficacy of ICIs in TNBC, overturning previous beliefs that breast cancer is generally insensitive to immunotherapy. This review summarizes recent advances regarding resistance types, molecular mechanisms, associated genes and pathways, the role of the tumor microenvironment, and clinical strategies related to immunotherapy resistance in the neoadjuvant setting of TNBC, aiming to provide insights and guidance for future research exploration and clinical practice.